The Impact of Oil Price Fluctuations on the Stock Prices of the Saudi Stock Market Sectors - Bengana, Ismail; Mili, Khaled; Brika, Said Khalfa (Journal of Posthumanism, 2025)
This research paper aims to know the extent of the impact of oil price fluctuations at the world level, before and after the Covid 19 pandemic, on the prices of the most important sectors of the Saudi stock market, where the co-integration methodology was used to verify the possibility of a long-term equilibrium relationship. After using various tests of stationarity, causality, etc., then proving the existence of this relationship, which means that there is a financial contagion between the oil sectors and the rest of the other sectors, and the Covid-19 pandemic had a profound impact at all levels.